2004
DOI: 10.1007/s00438-004-1033-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of genes encoding chromatin proteins in the archaeon Methanococcus voltae indicates their involvement in the regulation of gene expression

Abstract: Several genes for chromatin proteins are known in Archaea. These include histones and histone-like proteins in Euryarchaeota, and a DNA binding protein, Alba, which was first detected in the crenarchaeote Sulfolobus solfataricus and is thought to be involved in transcriptional regulation. The methanogenic archaeon Methanococcus voltae harbors four genes coding for all these three types of chromatin proteins. Deletion mutants for the two histone genes ( hstAand hstB), the gene encoding the histone-like protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…Mvo10b, for example, is a Sac10b chromatin protein from the mesophilic methanogenic archaeon Methanococcus voltae with an optimal growth temperature of ~37°C. Deletion of the mvo10b gene did not affect viability and growth of the mutant archaeon but changed the protein expression pattern relative to that of the wild-type as revealed by 2D gel electrophoresis of cell extracts [59]. Recently [60], we cloned and expressed recombinant Mvo10b in E. coli.…”
Section: Functional Divergence -Functions Of Sac10b Family Members Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Mvo10b, for example, is a Sac10b chromatin protein from the mesophilic methanogenic archaeon Methanococcus voltae with an optimal growth temperature of ~37°C. Deletion of the mvo10b gene did not affect viability and growth of the mutant archaeon but changed the protein expression pattern relative to that of the wild-type as revealed by 2D gel electrophoresis of cell extracts [59]. Recently [60], we cloned and expressed recombinant Mvo10b in E. coli.…”
Section: Functional Divergence -Functions Of Sac10b Family Members Inmentioning
confidence: 99%
“…It is interesting that the expression levels of these proteins are positively correlated with methanococcal optimum growth temperatures. The fact that both Mma10b and Mvo10b constituted only ~0.01 % each of the total cellular protein suggested that these mesophilic proteins participated in the regulation of distinct genes but it cannot be excluded that they are also involved in the regulation of chromatin structure [42,59] and that the two functions overlap.…”
Section: Functional Divergence -Functions Of Sac10b Family Members Inmentioning
confidence: 99%
“…A few homologs of eukaryal transcriptional regulators (33) and unique archaeal regulators (57) as well as non-sequencespecific DNA binding proteins (5,30) have been investigated for their contribution to the regulation of archaeal genes.…”
mentioning
confidence: 99%
“…The number of peptide pairs collected per ORF was designated n. The relative signal intensity (peak height) of 14 N and 15 N peptide peaks in each peak pair was used as a measure of relative peptide level. Multiple measurements of one protein were averaged to obtain the relative protein levels in S2 and S590.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the readily available genetic systems in mesophilic methanococci are of value for the investigation of the in vivo role of the Sac10b family. Heinicke et al (14) constructed a mutant of the mesophilic, heterotrophic Methanococcus voltae with a deletion of the gene encoding a Sac10b homolog. While the mutation did not affect growth in complex medium, two-dimensional gel electrophoresis of the cellular proteins identified changes in the expression of genes encoding a helix-turn-helix DNA binding protein, a cystathione ␤-synthase domain-containing protein, and pyruvate oxidoreductase (Por) subunit C (14).…”
mentioning
confidence: 99%